Autoantibodies against the C-terminus of Lipopolysaccharide binding protein are elevated in young adults with psychiatric disease. (April 2021) - Just, David; Rasmusson, Annica J.; Nilsson, Peter; Noreland, Maria; Malmström, Emma; Brodin, Petter; Månberg, Anna; Cunningham, Janet L.
Abstract: Growing evidence implies interactions between infections, the immune system and vulnerability for psychiatric disease. This study applies an affinity proteomic-based method to investigate potential disease associated autoantibody signatures in serum from patients from the "Young Adults" section of the Department of General Psychiatry at Uppsala University Hospital (n = 395) and population-based controls (n = 102). We found serum levels of antibodies against Lipopolysaccharide Binding Protein (LBP), a protein that is important for mediating innate immune responses involving the toll-like receptor-4 (TLR-4), to be higher in patients compared to controls (Mann Whitney U -test p  = 5.248 × 10 −10 ). The patients were divided into three groups based on their relative levels of autoantibodies against LBP. The distribution of autism spectra disorders ( p  = 2.0 × 10 −4 ) and hospital care for an infection as adults ( p  = 0.036) differed between the anti-LBP groups, with low incidence in the group of patients with the highest levels of anti-LBP who were diagnosed with primarily affective and anxiety disorders. In a sub-group analysis, the controls who screened positive for current or previous psychiatric diagnosis (n = 20) had higher anti-LBP compared to non-psychiatric controls with negative screening for psychiatric disorders (Mann Whitney U -test p  = 0.006). Inflammatory markers were found to differ across anti-LBP groups and several pro-inflammatory markers, including IL-1β, were low in patients with high anti-LBP and serum LBP levels were lowest in patients with the highest levels of antibodies against LBP ( p  = 3.5 × 10 −5 ). A cell-based model showed that polyclonal rabbit anti-LBP, obtained through purification via the same protein fragment used in the initial autoantibody analysis, could interfere with LBP signaling since addition of anti-LBP to the assay reduced both IL-1β and IL-6 release from activated monocytes in response to LBP and LPS ( p  = 0.0001 and p  = 0.02). This novel finding of antibodies against LBP, where high levels were only found in young adults with psychiatric disease, merits further study. Our results suggest that these antibodies may have relevance for TLR4 based immune responses and vulnerability for both infection and psychiatric disorders. Highlights: Autoantibodies identified against Lipopolysaccharide Binding Protein (anti-LBP). Anti-LBP was more prevalent in psychiatric patients than controls. Inflammatory markers are lower in patients with high anti-LBP levels. A cell-based model supports an immunomodulatory function for anti-LBP.